2020
DOI: 10.3390/agronomy11010045
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance and Genetic Stability of Micropropagated Gooseberry Plants (Ribes grossularia L.)

Abstract: Gooseberry (Ribes grossularia L.) is a small fruit crop producing valuable fruits, which is constantly gaining importance. In vitro propagation of this species can significantly support the production of virus-free planting material and accelerate the introduction of new cultivars to the market. The aim of presented study was to assess field performance and genetic stability of micropropagated plants (MPs) of four gooseberry cultivars, “Captivator”, “Hinnonmaki Rot”, “Invicta”, and “Resika”. The growth vigor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…It is an efficient, quick, and reproducible technique in which the targets are the DNA fragments located between adjacent microsatellite regions, while the RAPD-PCR targets are random [18]. Wójcik et al [19] used ISSR primers to observe the genetic stability of regenerated plants of Ribes grossularia L. Both techniques are used together to obtain more realistic and accurate results [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is an efficient, quick, and reproducible technique in which the targets are the DNA fragments located between adjacent microsatellite regions, while the RAPD-PCR targets are random [18]. Wójcik et al [19] used ISSR primers to observe the genetic stability of regenerated plants of Ribes grossularia L. Both techniques are used together to obtain more realistic and accurate results [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This observation agrees with that of Mirzaei et al [75] concluded that true-to-typeness of micropropagated olive was cultivar-dependent using partec flow cytometry (FCM) and AFLP analysis. Also, Wójcik et al [76] employed two DNA-based approaches to assess genetic stability of micropropagated plants, amplified fragment length polymorphism (AFLP) and inter simple sequence repeat (ISSR), and found no polymorphism among the analyzed gooseberry cultivars. Other plant species with consistent genetic fidelity in in vitro regenerates include Prunus ulcis [77], Brassica oleracea [78], and Rhodiola imbricate [79].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-topolin enabled shoot elongation as well as efficient rooting and acclimatization. e ISSR and AFLP analyses showed that the method of in vitro propagation of gooseberry used in their research was suitable for obtaining plants with high genetic fidelity (Wójcik et al, 2021). Application of mT enabled the initiation and propagation of shoots in in vitro cultures of black currant for polyploidization and then for the propagation of the obtained tetraploids (Podwyszyńska & Pluta, 2019).…”
Section: Other Small Fruit Plantsmentioning
confidence: 99%